english The Effect of Giving Keji Beling (Strobilanthes crispa (L.) Blume) Leaf Extract on the Number of Blood Profiles in White Rats (Rattus norvegicus) Induced by Sodium Benzoate - Apriani, Hajijah; Tambunan, Efrida Pima Sari; Syukriah, Syukriah (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2024)
Sodium benzoate contains dangerous substances including the chemicals benzene, benzoic acid and sodium hydroxide. As a result of these dangerous contents, it can affect blood components such as erythrocytes, hemoglobin, leukocytes and platelets. The effects caused by food preservatives can be prevented by living a healthy lifestyle and using herbal plants as medicinal therapy. One of them is by using natural ingredients, namely keji shard leaves. This study aims to determine keji beling leaf extract on the number of erythrocytes, hemoglobin, leukocytes and platelets due to food preservatives. The stages in this research include phytochemical screening, observing the number of erythrocytes, hemoglobin, leukocytes and platelets. Data analysis used one way ANOVA and Duncan's test. The results of the study showed that administration of sodium benzoate had an effect on increasing the number of erythrocytes 24.35 ± 0.62, hemoglobin 68.0 ± 2.5, leukocytes 21.80 ± 1.68 and platelets 591.7.8 ± 10.5. Meanwhile, administration of keji beling leaf extract can reduce the number of erythrocytes by 13.00 ± 0.18b, hemoglobin by 26.2 ± 2.2b, leukocytes by 13.00 ± 0.74b and platelets by 353.0 ± 09.4b. The optimal dose of keji beling leaf extract to reduce the number of erythrocytes, hemoglobin, leukocytes and platelets is a dose of 500 mg/kg BW